Interprofessional Collaboration in the Operating Room: A Nursing Perspective - Levesque, Marie-Julie (Université d'Ottawa / University of Ottawa, 2021)
The aim of this thesis was to examine the contribution of nurses to interprofessional collaboration (IPC) in the operating room (OR) guided by the Interprofessional Education Collaborative Patient Care Practice (IECPCP) framework. First, a secondary analysis of interviews with 19 registered nurses was conducted. Twenty emergent themes were identified. The most prevalent of the four dimensions (internalization; shared goals and vision; governance; and formalization) consisted of the internalization dimension relating to human interaction and sense of belonging within the interprofessional team. A scoping review then identified 20 studies evaluating four interventions (briefings, checklists, team training, and debriefings) used to improve IPC in the OR. Despite weak study designs, these interventions showed improvements in communication, teamwork, and safety outcomes. OR nurses contribute mainly through interactional processes and they require organizational support to foster their efforts in IPC. Nurse are involved in all IPC interventions and their contribution is important to support IPC in the OR.
Keywords: Interprofessional; Interprofessional relations; Interdisciplinary; Multidisciplinary; Collaboration; Teamwork; Operating room